BORN GLOBALS AND ENTREPRENEURIAL MARKETING STRATEGIES: A CASE STUDY IN PORTUGAL AND FINLAND - Castela, Maria Teresa (My University, 2014)
The aim of this study is to investigate in what way Born Global companies apply Entrepreneurial Marketing strategies and which factors influence these. For that purpose, the analysis focuses on the extent to which these firms are likely to adopt Entrepreneurial Marketing strategies and its most important dimensions. In addition, the effects of previous experience and knowledge as well as national culture of the founding teams and effectuation decision-making are researched. The present study is qualitative. In total, six design companies from Portugal and Finland were analyzed, meaning there are three case companies from both countries. The results suggest that design firms have unique characteristics. Previous experience proved to have a positive effect on entrepreneur’s motivation to create a business. Effectuation decision-making was largely adopted by the case companies. The relationship between national culture and entrepreneurship proved not to be significant. The findings of this research contribute to the understanding of Born Global firms and Entrepreneurial Marketing by focusing on two settings still insufficiently studied: design companies and the Portuguese environment.
Keywords: Entrepreneurial Marketing; Born global; Effectuation; Founding team; Design.; fi=Master's Degree Programme in International Business|